Dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate as a designer substrate in the syntheses of important heterocyclic scaffolds - Pandey, Ganesh; Gaikwad, Amrut L.; Gadre, Smita R. (Asian Journal of Organic Chemistry, 2012)
Designed scaffold dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate was synthesized in optically pure form by photoinduced one-electron reductive beta-activation of an alpha,beta-unsaturated carbonyl moiety for stereoselective C-C bond formation. Use of the morpholine derivative as a ``chemical multitalent'' is demonstrated by its easy transformation to valuable heterocyclic building blocks such as methyl [(2R,3S)-3-hydroxy-5-oxopyrrolidin-2-yl]acetate, methyl [(2R,3S)-3-amino-5-oxotetrahydrofuran-2-yl]acetate, (3R,4S)-4-aminohexane-1,3,6-triol, and 2-[(2R,3S)-3-aminotetrahydrofuran-2-yl]ethanol.
Keywords: Amino alcohols; butyrolactams; butyrolactones; morpholines; photoinduced electron transfer reactions